FAKTOR-FAKTOR YANG MEMENGARUHI MANAJEMEN LABA PADA PERUSAHAAN NON-KEUANGAN - PUTRI NOVELIA; Kartina Natalylova (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study is to obtain empirical information about the effect of audit comittee, independence of board of directors, firm size, board size, leverage, managerial ownership, institutional ownership, and audit quality. This study uses samples from all non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. The results of the sample found that there were 79 companies. The results of this study indicate that the independence of board of directors and audit quality have an effect on earnings management, that earnings management practices will be higher because the demands of good prospect reports in the public make companies with high growth motivated to carry out earnings management. However audit comittee, firm size, board size, leverage, managerial ownership and institutional ownership have no effect on earnings management.